Object Localization Does Not Imply Awareness of Object Category at the Break of Continuous Flash Suppression - Kobylka, Florian; Persike, Malte; Meinhardt, Günter (Frontiers in Human Neuroscience, 2017)
In continuous flash suppression (CFS), a dynamic noise masker, presented to one eye, suppresses conscious perception of a test stimulus, presented to the other eye, until the suppressed stimulus comes to awareness after few seconds. But what do we see breaking the dominance of the masker in the transition period? We addressed this question with a dual-task in which observers indicated (i) whether the test object was left or right of the fixation mark (localization) and (ii) whether it was a face or a house (categorization). As done recently (Stein et al., 2011), we used two experimental varieties to rule out confounds with decisional strategy. In the terminated mode, stimulus and masker were presented for distinct durations, and the observers were asked to give both judgements at the end of the trial. In the self-paced mode, presentation lasted until the observers responded. In the self-paced mode, b-CFS durations for object categorization were about half a second longer than for object localization. In the terminated mode, correct categorization rates were consistently lower than correct detection rates, measured at five duration intervals ranging up to 2 seconds. In both experiments we observed an upright face advantage compared to inverted faces and houses, as concurrently reported in b-CFS studies. Our findings reveal that more time is necessary to enable observers judging the nature of the object, compared to judging that there is “something other” than the noise which can be localized, but not recognized. This suggests gradual transitions in the first break of CFS. Further, the results imply that suppression is such that no cues to object identity are conveyed in potential “leaks” of CFS (Gelbard-Sagivet al., 2016).